Financial inclusion initiative through Malays Family Associations: a survey from Islamic wealth management’s perspective - Mohd. Zain, Nor Razinah; Ab. Rahman, Asmak; Mohd Noor, Azman (2020)
The basic unit of a society can be easily referred to the family unit. The normal family unit usually consists of a father, a mother, and children. With the expansion of the family members such as through marriages, adoptions, and the birth of new generations, the family unit continues to grow. Such expansion eventually gives impacts to the family unit’s social, economic development, and wealth accumulation. The rapid expansion of family unit is very often led to loss of communication and identification of the family members due to the existence of generation gap. In Malaysia, there is a practice of having family association where the family members that shared the same ancestral root stay together as a family and help each other in facing any existence of financial stress. Depending on a qualitative research and open-ended survey interviews, This research is carried out to investigate financial inclusion initiative through Malays family associations. The interview has been conducted with two Malays family associations. The researchers also evaluate their findings through an Islamic wealth management perspective. It is found that deeply rooted from the concept of Ukhwah (brotherhood), the Malays family associations continue to exist in Malaysian society.